בין הסימבולי לסמיוטי במחקריו של דן מירון - אופנהיימר יוחאי (מכאן, 2020)
The twin concepts of the symbolic and the semiotic are frequently used in Dan Miron’s literary research. On the one hand, this points to the theoretical background which is prevalent in his writings, and on the other hand to a significant change which took place in Hebrew literary thought over the last two decades, and to which Miron gave full expression. Julia Kristeva made the distinction between the symbolic, which relates to language as a normative and meaningful system of signs, and the semiotic, which indicates the chaotic, amorohous and unruled drives and urges which are present under the surface of consciousness. With the help of these concepts, the works of Dan Miron can be divided into two groups: those in which he attempts to locate the symbolic order in literary works; and those in which he traces the semiotic and defines the poetics typical of group of texts. at the same time, two different historiographical attitused can be identified in Miron’s research. The first focuses on the canonic literature and asks questions about influence and periodization, thereby presupposing a linear and casual development. The other historiographical attitude focuses on the coexistence of different poetical values which are not hierarchical or exclusive but complementary.